Cengklik Reservoir Tourism Development with approach Eco-Waterfront - Auliya Rohmah Ramadhani; Budi Prayitno; Wiwik Setyaningsih (Journal of Infrastructure & Facility Asset Management, 2021)
Reservoir tourism is tourism that is widely associated with activities in water, such as lakes and rivers which are managed in an integrated and planned manner, so that they are ready to receive tourist visits. So far, the existence of reservoir tourism which is unique has not been handled and managed optimally. This trend can be seen in several reservoir areas that have lost their original character, and have even disappeared and changed their function due to neglect. Among them is the Cengklik Reservoir. So one of the initial measures is to identify the potential for reservoir tourism areas to be developed through the Eco-Waterfront Architecture Approach by paying attention to the surrounding natural environment and the function of the area.The purpose of this research is to formulate a tourism development strategy through the Eco-Waterfront Architecture approach. The formulation is based on the exploratory descriptive method, and the physical spatial mapping of the character of the area, as well as the social and cultural mapping. The final result is the formulation of the development of Cengklik Reservoir Tourism that is environmentally friendly and sustainable.